(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to highlight the role of auditors at the Financial Control Bureau in assessing the extent of the company’s compliance with health, safety, and environmental requirements within the refinery during its daily operations to ensure the safety of employees. Data was collected based on the information provided in the financial control bureau’s reports related to Al-Dora Company for the years (2016-2019). The descriptive-analytical approach was employed in conducting the research. The study arrived at several results, the most important of which is that auditors play an active role in assessing the performance, efficiency, and effectiveness of occupational health and safety in the researched company. Additionally, a number of indicators were identified to assess the level of risks associated with this performance in the company.